Perjuangan KH. Ghalib dalam Penerapan Pendidikan Karakter di Pringsewu, Lampung - Dwi Gesti Jayanti; Dyah Kumalasari; Suranto Suranto (CHRONOLOGIA, 2022)
Indonesia's struggle against the colonial powers, namely Japan and the Netherlands, began in the period between 1945 and 1949. In this case, the previous fighters fought for all their souls and bodies to seize and defend the Unitary State of the Republic of Indonesia from the shackles of the colonial invaders. Not only that, the economic, social, and psychological conditions were felt by the community and had a very large impact due to colonialism. The call of his conscience does not make him waver, the spirit does not waver, even though life is a bet between life and death at the last drop of blood. The generation of young people, especially students or students, is expected to be able to regenerate the values "‹"‹of the struggle of a figure who has fought for Indonesian independence, one of which is the struggle of a KH figure. Ghalib in Pringsewu, Lampung Province. The research aims to identify specifically the Struggle of KH. Ghalib in the Application of Character Education in Pringsewu Lampung. This study uses a qualitative descriptive research method, with a biographical approach. The struggle of KH. Ghalib is one of the fighters from Pringsewu Lampung, along with other fighters fighting in the way of Allah, with Laskar Hezbollah, Sabillah, and Garuda Hitam fighters for the benefit of the people, defending the truth, and seizing independence from the Dutch colonialists. The exemplary values "‹"‹of struggle from the figure of KH. Ghalib can be a role model for the younger generation, especially for students or students. The values "‹"‹of the struggle of KH. Ghalib can be implemented in the application of character education in Pringsewu Lampung, one of which is always doing good, respecting the sick, maintaining inter-religious harmony, and being responsible for the interests of the people.